Decision Support System for Promotion Selection using the Multi Factor Evaluation Process Method - Firdaus (Journal of Computer Scine and Information Technology, 2022)
Company PT. ALS is a ground transportation service company that transports passengers between cities and provinces. Buses from PT. ALS has been a mainstay and pride of the community, especially in its timely service in taking passengers to their destination. Promotion at PT. Currently, the ALS assessment process for selecting employee promotions is carried out by supervisors in each division who directly evaluate employee performance. Then in the process of selecting the position of the candidate who has the highest score based on certain criteria who will occupy the required position in accordance with the required criteria. Data calculations are done manually using Microsoft Excel but have not used the computer system optimally. The basis for this research is to help PT. ALS in making a decision in selecting employee promotions. Position is a group of positions that are almost the same in an agency, institution or company. For employees, the results of the assessment can be used as feedback on work performance, so that they have a basis for consideration for planning their career development. This research will be conducted using the Multi Factor Evaluation Process method by processing several criteria for decision making. Meanwhile, on the other hand, the results of this assessment can be used by the company to base decision-making in terms of reward system (compensation), promotion, training and career planning.